Exploring the technical and economic viability of lignocellulosic waste briquettes from the wood panel industry - Souza, André Gustavo Oliveira [UNESP]; Eufrade-Junior, Humberto de Jesus; Spadim, Emanuel Rangel [UNESP]; Guerra, Saulo Philipe Sebastião [UNESP]; Esperancini, Maura Seiko Tsutsui [UNESP] (Elsevier, 2024)
The production process for reconstituted wood panels involves a sequence of operational steps that generate substantial lignocellulosic waste, often discarded in landfills. This study aimed to assess the technical and economic viability of utilizing these wastes submitted to the briquetting process as an alternative source to meet the energy demand of industrial boilers. In order to achieve the proposed objective, two technological pathways were evaluated, as well the fuel characteristics of the waste briquettes. Also, operational data was collected on the briquetting process and transportation to supply the boiler. Thus, the economic indicators were analyzed deterministically, and the net present value was analyzed under risk conditions using the Monte Carlo method. The findings revealed that briquettes derived from waste in panel industries exhibited twice the net energy density (5.2 – 5.9 GJ kg−1) of traditional woodchips (0.7 – 2.6 GJ kg−1), offering a potential enhancement to system efficiency. Furthermore, the briquetting process demonstrated advantages in transporting materials over extended distances. From an economic standpoint, the investment in the briquetting plant exhibited a payback period of 3 years, a high internal rate of return (43.49%), and low investment risk, primarily attributed to the rising wood chip prices in the market. These results underscore the potential of this approach to contribute to the production of environmentally friendly wood panels. The Monte Carlo method offered an alternative approach to illustrate the potential for reducing risk rates and enhancing forecast reliability in production planning for bio-briquettes.
Keywords: Analyze risk; Eucalyptus spp.; Fuel quality; Net present value; Technological routes